Penerapan Model Pembelajaran Problem Solving Dalam Meningkatkan Hasil Belajar Matematika Siswa - Erni Sulistiyanti; Sinta Nuriyah; Siti Sarah (JPT : Jurnal Pendidikan Tematik, 2025)
The problem in this study is the low achievement of students' mathematics learning. This problem can be formu- lated as follows "How is the application of the Problem Solving learning model in Improving Mathematics Learning Outcomes?. The aim of the research is to describe the application of the Problem Solving learning model in Im- proving Students' Mathemat- ics Learning Outcomes. The focus in this Classroom Action Research is the Application of the Problem Solving learning model and Mathematics Learning Outcomes. The research subjects were students. Data collection techniques in this study were interviews and tests. Data analysis techniques are data reduction, data presentation, conclusion drawing. The results of the study show that the application of the Problem Solving learning model can improve students' mathematics learning out- comes.